Rational synthesis, crystal structure, and sensing and adsorption properties of luminescent metal–organic frameworks. Issue 33 (23rd July 2019) - Fan, Chuanbin; Zong, Ziao; Meng, Xiangmin; Zhang, Xia; Zhang, Xiaoyin; Zhang, Dongmei; Xu, Cungang; Wang, Hu; Fan, Yuhua
Abstract : Five novel Cd(ii ) metal–organic frameworks (Cd-MOFs) were synthesized employing a rational design approach under solvothermal conditions. The luminescence sensing and the targeted dye adsorption properties of the MOFs1–5 are investigated. Abstract : Five novel Cd(ii ) metal–organic frameworks (Cd-MOFs), namely [Cd6 (L)4 (1, 3-bit)2 (H2 O)4 ] n (1 ), [Cd(HL)(4, 4′-bbibp)] n (2 ), [Cd3 (L)2 (1, 4-bimb)2 (H2 O)2 ] n (3 ), [Cd(HL)(4, 4′-bidpe)] n (4 ) and [Cd3 (L)2 (1, 1′-bbi)(H2 O)4 ] n (5 ) (flexible H3 L = 5-(2-carboxylphenoxy)isophthalic acid, rigid 1, 3-bit = 1, 3-bis(l-imidazoly)toluene, rigid 4, 4′-bbibp = 4, 4′-bis(benzoimidazo-1-ly)biphenyl, semi-flexible 1, 4-bimb = 1, 4-bis(imidazol-l-ylmethyl)benzene, semi-flexible 4, 4′-bidpe = 4, 4′-bis(imidazolyl)diphenyl ether, and flexible 1, 1′-bbi = 1, 1′-(1, 4-butanediyl)bis(imidazole)) were synthesized employing a rational design approach under solvothermal conditions and further characterized by elemental analysis, IR spectra, thermogravimetric (TG) analysis, powder X-ray diffraction (PXRD), and single-crystal X-ray diffraction. Diversity architectural topologies have been generated by adjusting the N-donor ligands. They exhibit varied structures:1 displays an unprecedented 6-nodal (3, 3, 4, 4, 8, 8)-c 3D topology framework with the point Schläfli symbol of (3·4·5)2 (3 2 ·4 2 ·5 2 ·6 6 ·7 8 ·8 7 ·9)(3 2 ·6 3 ·7)(4·6 4 ·8)(4 10 ·6 11 ·8 7 )(4 3 )2 ;2 shows a 2-fold interpenetrating 4-connectedcds topology with the point Schläfli symbol of (6 5 ·8);3 exhibits an unprecedented 2-nodal (3, 8)-c 3D topology network with the point Schläfli symbol of (4 2 ·5)2 (4 4 ·5 6 ·6 10 ·7 5 ·8 2 ·9);4 shows a 4-connectedsql topology with the point Schläfli symbol of (4 4 ·6 2 );5 displays atfz-d topology 2-nodal (3, 8)-c 3D network with the point Schläfli symbol of (4 3 )2 (4 6 ·6 18 ·8 4 ). The luminescence studies reveal that MOFs1–5 display highly sensitive and selective fluorescence sensing towards Fe 3+ cations, CrO4 2− anions and molecular acetone. Meanwhile, the targeted dye adsorption properties of MOFs1–5 are investigated.